Oyapock et Maroni Portraits d'estuaires - Gardel, Antoine (éditions Quae, 2021)
Guyana, delimited by its border rivers, the Oyapock and the Maroni, is a French Amazonian territory in South America, remarkable for its rich biodiversity. The Guyanese coastline, which stretches for 350 km between the estuaries of these two rivers, is extremely unstable, constantly modified by mud banks formed by sediments carried from the Amazon delta in Brazil which move along sides. One of the best preserved mangroves in the world is developing there, at the heart of considerable ecological challenges due to its role as nursery and nursery for many species and its ability to store carbon. Very productive in terms of fishing, the Guyanese maritime fringes are under heavy pressure on fishery resources while numerous socio-environmental changes are taking place under the effect of strong demographic growth and significant human migration. Guyana must therefore meet many environmental, human and economic challenges today. This richly illustrated book is both a showcase of the Guyanese coastline and these exceptional estuaries, and an invitation to rethink the interactions between man and his environment.